ANTARA KESEMPATAN DAN KETERBATASAN: STATUS SOSIAL EKONOMI KELUARGA DAN CAPAIAN PENDIDIKAN ANAK - Sifa Alfadila, Nadya Fatika, Eka Syifa Andrini, Yusran Rabbani Fandika, Syifa Almanda, Arif Saefudin (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
This study examines the relationship between family socioeconomic status and children's educational attainment in low-income communities. The research stems from the persistent educational inequality in Indonesia, largely influenced by family economic conditions. Using a qualitative case study design conducted in Sudimara Barat, Tangerang, data were collected through in-depth interviews, observations, and documentation, then analyzed thematically. The results show that economic limitations affect access to education, learning facilities, and opportunities for higher study. However, social support from parents, teachers, and peers helps sustain students’ learning motivation and serves as a balancing factor amid financial constraints. The study reveals that educational inequality is shaped not only by economic factors but also by the lack of social and cultural capital within families. Theoretically, it contributes to the sociology of education by exploring the interaction between economic, social, and cultural capital. Practically, it recommends more inclusive and information-based educational policies to improve access and equity for low-income families.